Mechanisms Underlying Improvement in Obstructive Sleep Apnea Syndrome by Uvulopalatopharyngoplasty. (6th June 2017) - Yamamoto, Takahisa; Fujii, Naoko; Nishimura, Yoichi; Iwata, Noboru; Nakata, Seiichi
Abstract : In a previous case report, we determined for the first time that uvulopalatopharyngoplasty (UPPP) does not change the volume of the upper airway but causes morphological changes in the entire upper airway. The objective of this study is to elucidate the mechanisms underlying the improvement in obstructive sleep apnea syndrome (OSAS) by UPPP. We present an additional case involving a patient with OSAS treated using UPPP. Morphological and numerical parameter changes after surgery were compared with the corresponding preoperative values. Anatomically accurate upper airway computational models were reconstructed from computed tomographic imaging data. In addition, computed fluid dynamics analysis was performed to reveal inhalation flow characteristics before and after UPPP and clearly assess the effect of UPPP on airflow patterns in the patient's upper airway. An important benefit of UPPP is the morphological changes in the entire upper airway, in addition to widening the restricted area. These morphological changes induce laminarization of the pharyngeal jet. To obtain sufficient efficacy of UPPP in OSAS, the morphological changes in the upper airway and the airflow pattern after the surgery must be controlled.